2017
DOI: 10.1111/een.12440
|View full text |Cite
|
Sign up to set email alerts
|

Location of bumblebee nests is predicted by counts of nest‐searching queens

Abstract: * Bumblebee nests are difficult to find in sufficient numbers for well replicated studies. Counts of nest-searching queens in spring and early summer have been used as an indication of preferred nesting habitat, but this relationship has not yet been validated; high densities of nest-searching queens may indicate habitat with few nesting opportunities (meaning that queens have to spend longer looking for them).  * From mid April 2010, queen bumblebees were counted along twenty transects in grassland and woodla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…However, comparisons among studies are ultimately hampered by differences in survey efforts, and thus, differences in detection error. For example, low-intensity free searches by researchers or volunteers produced estimates of nest density ranging from 1.4 to 3.6 nests·ha −1 similar to the range of nest densities discovered by bumble bee “sniffer dogs” (O’Connor et al 2012, 2017). Both of these studies acknowledge that detection error is likely substantial for these methods.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, comparisons among studies are ultimately hampered by differences in survey efforts, and thus, differences in detection error. For example, low-intensity free searches by researchers or volunteers produced estimates of nest density ranging from 1.4 to 3.6 nests·ha −1 similar to the range of nest densities discovered by bumble bee “sniffer dogs” (O’Connor et al 2012, 2017). Both of these studies acknowledge that detection error is likely substantial for these methods.…”
Section: Discussionmentioning
confidence: 64%
“…Since colonies are the functional unit of the population for social insects such as bumble bees, studies of nesting habitat are particularly valuable for conservation planning. Yet, colonies are difficult to find, so relatively few studies have investigated the correlates of nest density compared to the numerous studies of habitat preference by foraging workers (but see examples in Harder 1986; Osborne et al 2008; Waters et al 2010; Lye et al 2012; O’Connor et al 2012, 2017). This disparity is problematic because workers are highly mobile, e.g., workers often forage up to 1 km from their colony (Greenleaf et al 2007) and may be attracted to areas rich in floral resources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, grassland is mainly visited by badgers in wet conditions when foraging for their primary prey item, L. terrestris (Kruuk & Parish, ; Shepherdson et al, ). Bumblebees also utilize these two habitats, for nesting (O'connor, Park, & Goulson, , ; Osborne et al, ) and foraging (Carvell et al, ). A number of studies show that bumblebees nest at similar densities in woodland and grassland habitats in the UK (Woodland: 10.8–27.78 ± 13.33 nests/ha [O'connor, Park, & Goulson, ; O'Connor, Park, & Goulson, ; Osborne et al, ]; Grassland: 11.4–14.8 nests/ha [Osborne et al, ]), although other work has shown bumblebee and pollinator abundance is often negatively impacted by woodland (Diaz‐Forero et al, ).…”
Section: Introductionmentioning
confidence: 99%